Small-scale food producers in Serbia: the use of Facebook in the market - Sljukic, Marica; Sljukic, Srdjan; Vidicki, Vladan (Sociološki pregled, 2022)
The problem of small-scale food producers in Serbia is relatively recent and still insufficiently approached in sociological research, so this paper aims to provide a specific exploratory contribution. There is partial insight into this issue in terms of sociology of organizations and rural sociology; accordingly, the starting point for this analysis is a theoretical basis that is comprised of relevant theoretical views, which have been formed within the said sociological disciplines. The analysis includes the communication among various participants in the Facebook group Small-scale food producers in Serbia. The selected method is the qualitative content analysis with a focus on the thematic analysis. In the analysis, the following cognitive objectives have been set: 1) identifying major features of the small-scale food producer category in Serbia; 2) establishing their competitive advantage in the market; 3) identifying the characteristics of consumers for these producers‘ products and 4) identifying broad (the broadest) social factors that encourage and/or inhibit the functioning of this category of food producers.